Chapter 3 Boxer cool - Lewandowski, Joseph D (Taylor & Francis, 2022)
This chapter examines the apparent look of nonchalance evinced by boxers in the face of danger and harm-what is characterized as 'boxer cool'. It is argued that boxer cool is a culturally derived repertoire of looks, stances and gestures acquired over time, and crucial to navigating lived structural and physical violence. In boxer cool, elements, lessons, and know-how from the world of 'the hood' are recalibrated and effectively redeployed in the context of training and competing in the sport of boxing. Boxer cool is derivative of a milieu where individuals must learn to self-manage the complex emotional states and potential conflicts continually emergent in the physical and structural violence endemic to their daily life. Boxer cool thus finds its immediate origins not primarily in the gym or ring but in the necessary cultivation of sophisticated orientations, coping mechanisms, and practices of self-management in persistently dangerous and harmful contexts.